Journalism and Foreign Aid in Africa - Paterson, C.; Gadzekpo, A.; Wasserman, H. (African Journalism Studies, 2018)
This essay introduces the Special Issue. The authors briefly survey the contemporary and complex relationship between aid and journalism and the role of foreign aid/development assistance in shaping African media systems. A call is made for greater research into the aid and journalism relationship and the impact these processes have on fostering independent national media sectors in Africa.
Keywords: Democratisation; Development assistance; Journalism education; Journalism norms; Media development; Post- colonial critique